2003
DOI: 10.1037/1040-3590.15.3.413
|View full text |Cite
|
Sign up to set email alerts
|

A Multisite Comparison of Actuarial Risk Instruments for Sex Offenders.

Abstract: Four actuarial instruments for the prediction of violent and sexual reoffending (the Violence Risk Appraisal Guide [VRAG], Sex Offender Risk Appraisal Guide [SORAG], Rapid Risk Assessment for Sex Offender Recidivism [RRASOR] and Static-99) were evaluated in 4 samples of sex offenders (N = 396). Although all 4 instruments predicted violent (including sexual) recidivism and recidivism known to be sexually motivated, areas under the receiver operating characteristic (ROC) were consistently higher for the VRAG and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
235
4
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(260 citation statements)
references
References 49 publications
19
235
4
2
Order By: Relevance
“…Sex offending was not specifically associated with psychopathy among male prisoners. This is consistent with several previous studies in which psychopathy was not associated with sex offending (Gretton, Mcbride, Hare, O'Shaughnessy, & Kumka, 2001;Långströ m & Grann, 2000) and is only a moderate predictor of sexual recidivism (Hare, 2003;Harris, Rice, Quinsey, Lalumière, & Boer, 2003;Porter, Woodworth, Earle, Drugge, & Boer, 2003). In representative samples of sex offenders, paraphilias are likely to be of greater importance than the abnormal personality features and antisocial lifestyle measured by the psychopathy construct.…”
Section: Psychopathy and Offending Behavioursupporting
confidence: 91%
“…Sex offending was not specifically associated with psychopathy among male prisoners. This is consistent with several previous studies in which psychopathy was not associated with sex offending (Gretton, Mcbride, Hare, O'Shaughnessy, & Kumka, 2001;Långströ m & Grann, 2000) and is only a moderate predictor of sexual recidivism (Hare, 2003;Harris, Rice, Quinsey, Lalumière, & Boer, 2003;Porter, Woodworth, Earle, Drugge, & Boer, 2003). In representative samples of sex offenders, paraphilias are likely to be of greater importance than the abnormal personality features and antisocial lifestyle measured by the psychopathy construct.…”
Section: Psychopathy and Offending Behavioursupporting
confidence: 91%
“…Risk assessments are used to determine the sex offender's current level of sexual aggression and to possible predict future violent or sexual behavior [25]. Risk factors for sexual reoffending were classified, by consensus between the authors, into four categories based on the following criteria: supported, promising, possible, and unlikely [26].…”
Section: Assessment Of the Juvenile Sex Offendersmentioning
confidence: 99%
“…In addition, psychopathy as measured by the psychopathy checklist -revised (PCL-R: Hare 1991) is related to certain PDs, including antisocial PD, and also successfully predicts future aggression in a range of populations of criminals (Grettan et al 2001, Hill et al 2004. A final important finding is that anti-social PD and the PCLR makes significant contributions to the prediction of recidivism in a range of offences (Harris et al 2003). Therefore, from a number of points of view, research on PD has 9 been shown to produce extremely important findings in relation to the planning and development of services and treatment.…”
Section: Assessment Of Personality Disordermentioning
confidence: 99%
“…However, in mainstream sex offender work, inappropriate sexual preference and sexual drive have been suggested as primary motivation by several authors (Blanchard, Watson, Choy, Dickey, Klassen & Kuban 1999, Harris et al 2003. Although some of this work is beginning to extend to men with lower intellectual functioning, perhaps the main inferences can be drawn from studies which have noted previous sexual offending and patterns of offending in cohorts of referred clients.…”
Section: Sexual Preference and Sexual Drivementioning
confidence: 99%